REFLECTIONS ON THE HISTORY OF ROMANIAN FINANCIAL LAW - Cîrmaciu, Diana (International Journal of Legal and Social Order, 2025)
From the very outset of the present scientific undertaking, it must be emphasized that, given the wealth of information and the inherent complexity of the financial field, concerns related to the development of financial science were — and continue to be — fully justified. A study on the history of the broad domain of financial law allows for a deeper understanding and interpretation of its evolution, the topic being both current and relevant, as the history of financial law is closely connected to the evolution of the State and of the economic system